Peran Dinas Pemuda dan Olahraga dalam Membangun Minat Berolahraga di Kalangan Anak Muda - Candra Asnanto Putra; Afan Bagus Setyabudi; Ismi Iftikad (Lembaga Pengembangan Kinerja Dosen, 2025)
Sport is an activity that exists throughout the world and is an important aspect in a person's life. One of them, in Indonesia, sport plays an important role in increasing national success and resilience. The Youth and Sports Department has an important role in cultivating the younger generation's interest in sports. They can help young athletes develop their skills, provide guidance, and inspire them. This Field Work Practice Report aims to increase interest in sports among the younger generation. The objectives include organizing activities and programs to increase interest in sports, increasing national achievements by involving the younger generation in sports, increasing public awareness of the importance of sports, and increasing access to sports facilities through various activities and programs.